2015
DOI: 10.1590/0104-530x25298-14
|View full text |Cite
|
Sign up to set email alerts
|

Análise do impacto dos projetos de interação entre a UFRGS e a PETROBRAS

Abstract: Resumo Este trabalho tem o objetivo de analisar o impacto promovido por projetos de interação entre a UFRGS e a PETROBRAS, fomentados por fundos setoriais e incentivos governamentais. Com base em um levantamento e análise estatística multivariada, foram estudados projetos com foco em pesquisa e desenvolvimento (P&D) das unidades acadêmicas da UFRGS. Foram analisados a inovação e os impactos associados à origem dos projetos, demanda da empresa, iniciativa do pesquisador e antecedentes de pesquisa usando aná… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…The next paragraphs address the findings of each of these areas. The collaboration between universities and companies as a means to boost OI is the object of research of most of the studies identified (Alves & Pimenta-Bueno, 2014;Castro et al, 2014;Carrijo & Botelho, 2013;Closs & Ferreira, 2012;Fernandes et al, 2016;Gielfi et al, 2017;Matei et al, 2015;Oliveira & Balestrin, 2015;Schaeffer et al, 2015;Silva et al, 2013b;Stal & Fujino, 2016). Closs & Ferreira (2012) point out that university-company collaboration tends to be positive for companies because, in addition to reducing innovation costs, it also allows greater access to qualified people and university structures, especially laboratories.…”
Section: Presentation Of Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The next paragraphs address the findings of each of these areas. The collaboration between universities and companies as a means to boost OI is the object of research of most of the studies identified (Alves & Pimenta-Bueno, 2014;Castro et al, 2014;Carrijo & Botelho, 2013;Closs & Ferreira, 2012;Fernandes et al, 2016;Gielfi et al, 2017;Matei et al, 2015;Oliveira & Balestrin, 2015;Schaeffer et al, 2015;Silva et al, 2013b;Stal & Fujino, 2016). Closs & Ferreira (2012) point out that university-company collaboration tends to be positive for companies because, in addition to reducing innovation costs, it also allows greater access to qualified people and university structures, especially laboratories.…”
Section: Presentation Of Results and Discussionmentioning
confidence: 99%
“…Finally, in this area of collaboration university -company, Petrobras stands out as the company which leads university-company research (Alves & Pimenta-Bueno, 2014;Gielfi et al, 2017;Matei et al, 2015). In addition to its importance to Brazil, as reported by Gielfi et al (2017), this emphasis occurs mainly because Petrobras has an extensive network of scientific collaborations dispersed throughout the country.…”
Section: Presentation Of Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estes dois atores têm função complementar no processo de desenvolvimento tecnológico e na inovação. Da mesma forma, contribuem mutuamente para o alcance dos objetivos de ambos, mesmo que distintos (MATEI et al, 2015).…”
Section: Interação Universidade E Empresa E Contratos De Transferênci...unclassified